Family, kinship, and sympathy in nineteenth-century American literature - Weinstein, Cindy (Cambridge University, 2013)
In Family, Kinship, and Sympathy in Nineteenth-Century American Literature Cindy Weinstein radically revises our understanding of nineteenth-century sentimental literature in the United States. She argues that these novels are far more complex than critics have suggested, expanding the canon of sentimental novels to include some of the more popular, though under-examined, writers, such as Mary Jane Holmes, Caroline Lee Hentz, and Mary Hayden Green Pike. Rather than confirming the power of the bourgeois family, Weinstein argues, sentimental fictions used the destruction of the biological family as an opportunity to reconfigure the family in terms of love rather than consanguinity.